The Effect of Delivery Time on Customer Satisfaction in Cargo Services - Maesazshandy, Dava; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This study aims to analyze the impact of delivery time on customer satisfaction in cargo services. The research was conducted using a quantitative approach with a survey method. Data were collected from 150 respondents who are customers of various cargo service providers. The results indicate that delivery time significantly affects customer satisfaction. Timely deliveries lead to higher customer satisfaction, while delays result in dissatisfaction. The study concludes that improving delivery time can enhance customer satisfaction in cargo services.